Pengaruh Promosi Penjualan dan Celebrity Endorser terhadap Niat Beli Fashion Brand Lokal Giyomi pada Generasi Y dan Z - Dicky Adi Nugroho; Sri Setyo Iriani (Jurnal Ilmu Manajemen, 2020)
Marketing strategies change as technology develops. Marketers are demanded to be more creative in continuing to market their products so they will not be outdone by the times, fashion products are no exception. Giyomi is a local fashion brand that utilizes marketing with digital marketing using celebrity endorsers and offline marketing using sales promotions by holding bazaar tours and giving discounts for its products. however, this is still lacking interest among Y and Z generations because these generations prefer to use foreign brands such as ZARA and H&M. This research design to determine the effect of sales promotion and celebrity endorser on purchasing intentions on local fashion brands Y and Z generations (Study on the Giyomi brand). The sampling technique of this research used judgmental sampling and snowball sampling. The target population is generation Y and Z with criteria that use Instagram social media, of course, with a personal account that has followed Giyomi's Instagram account and knows Giyomi's promotion and celebrity endorser contained on Instagram social media. The number of samples of this study was 110 people. The results of this study indicate there is a significant positive influence between sales promotion and celebrity endorsers on purchasing intentions on local fashion brands Y and Z generations.